2018 15th International Conference on Control, Automation, Robotics and Vision (ICARCV) 2018
DOI: 10.1109/icarcv.2018.8581147
|View full text |Cite
|
Sign up to set email alerts
|

RCCNet: An Efficient Convolutional Neural Network for Histological Routine Colon Cancer Nuclei Classification

Abstract: Efficient and precise classification of histological cell nuclei is of utmost importance due to its potential applications in the field of medical image analysis. It would facilitate the medical practitioners to better understand and explore various factors for cancer treatment. The classification of histological cell nuclei is a challenging task due to the cellular heterogeneity. This paper proposes an efficient Convolutional Neural Network (CNN) based architecture for classification of histological routine c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, the handcrafted features limit the representation capabilities of nuclei entities. Recently, the nuclei classification models usually infer cell types based on the CNNs for nucleus segmentation (Zhang et al 2017;Basha et al 2018;Lou et al 2022Lou et al , 2023bMa et al 2023;Yu et al 2023) or nucleus centroid detection (Abousamra et al 2021;Huang et al 2023b). Graham et al (2019) propose a CNN of three branches, predicting nucleus types for the segmented nucleus instances.…”
Section: Related Workmentioning
confidence: 99%
“…However, the handcrafted features limit the representation capabilities of nuclei entities. Recently, the nuclei classification models usually infer cell types based on the CNNs for nucleus segmentation (Zhang et al 2017;Basha et al 2018;Lou et al 2022Lou et al , 2023bMa et al 2023;Yu et al 2023) or nucleus centroid detection (Abousamra et al 2021;Huang et al 2023b). Graham et al (2019) propose a CNN of three branches, predicting nucleus types for the segmented nucleus instances.…”
Section: Related Workmentioning
confidence: 99%
“…Among these models, the convolutional neural network (CNN) [14] has gained popularity due to its superior ability to classify features compared to manually designed ones. That's strategy applied in various image processing tasks, including image classification [15,16], object detection [17], semantic segmentation [18], colon cancer classification [19], depth estimation [20], face anti-spoofing [21], and related domains. Advanced techniques within the field of deep learning have been suggested for dealing with the problem of shifting domains in hyperspectral imaging (HSI).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results demonstrated that pre-trained VGG16 models utilizing transfer learning (i.e., the second and third VGG16 models) outperformed the supervised learning approach of the VGG16 which was fully trained from scratch. Basha et al [11] developed a CNN called RCCNet to classify colon cancer nuclei into four categories: miscellaneous, fibroblast, epithelial, and inflammatory. Their developed model was compared with various DL models: WRN, GoogLeNet, AlexNet, softmaxCNN, and softmaxCNN_IN27, and their proposed model achieved the best performance results.…”
Section: Introductionmentioning
confidence: 99%
“…The problem with detecting colon cancer using medical images depends on the datadriven methods used and the images generated by an imaging modality. Unlike previous studies that have focused on evaluating the performance behavior of DL models in terms of detecting colon cancer [8][9][10][11][12], our contributions can be summarized as follows:…”
Section: Introductionmentioning
confidence: 99%